Inovasi Pelayanan Administrasi Kependudukan berbasis Digital melalui Program Identitas Kependudukan Digital (IKD) di Dinas Dukcapil Kabupaten Tanah Datar - Zulmawati, Fira; Mubarak, Adil (Lembaga Yasin AlSys, 2025)
The implementation of the Digital Population Identity (IKD) program by the Ministry of Home Affairs targets 30% coverage of the eligible population; however, as of July 2025, realization in Tanah Datar Regency has reached only 17,530 individuals, or approximately 6.12%. This study aims to evaluate the extent to which the IKD program has been implemented as an innovation in population administration services and to identify its supporting and inhibiting factors. A qualitative method with a descriptive approach was employed, using interviews and document analysis as data collection techniques. The findings reveal that the implementation of IKD by the Civil Registration Office (Disdukcapil) in Tanah Datar has not fully met the innovation attributes outlined in Rogers’ theory. IKD presents a relative advantage through easier access, service efficiency, and improved security systems. In terms of compatibility, the innovation aligns with the needs of younger generations and civil servants but lacks inclusivity for the broader community. Ease of use (complexity) remains a barrier for elderly users and those with limited digital literacy. Trialability has been introduced gradually, though its utilization remains suboptimal, and observability is still low, as the benefits of IKD are not yet widely perceived. Supporting factors include relatively easy digital access, budget efficiency, and human resource competence. Conversely, major barriers include the digital divide, limited technological infrastructure, weak inter-agency integration, and low public adoption of digital population administration technologies. The study concludes that an acceleration strategy is needed, based on digital literacy enhancement, infrastructure expansion, and system integration, to improve the effectiveness of IKD implementation.